GluN2B-containing NMDARs in the mammalian brain: pharmacology, physiology, and pathology - Ge, Yang; Wang, Yu Tian (Frontiers in Molecular Neuroscience, 2023)
Glutamate N-methyl-D-aspartate receptor (NMDAR) is critical for promoting physiological synaptic plasticity and neuronal viability. As a major subpopulation of the NMDAR, the GluN2B subunit-containing NMDARs have distinct pharmacological properties, physiological functions, and pathological relevance to neurological diseases compared with other NMDAR subtypes. In mature neurons, GluN2B-containing NMDARs are likely expressed as both diheteromeric and triheteromeric receptors, though the functional importance of each subpopulation has yet to be disentangled. Moreover, the C-terminal region of the GluN2B subunit forms structural complexes with multiple intracellular signaling proteins. These protein complexes play critical roles in both activity-dependent synaptic plasticity and neuronal survival and death signaling, thus serving as the molecular substrates underlying multiple physiological functions. Accordingly, dysregulation of GluN2B-containing NMDARs and/or their downstream signaling pathways has been implicated in neurological diseases, and various strategies to reverse these deficits have been investigated. In this article, we provide an overview of GluN2B-containing NMDAR pharmacology and its key physiological functions, highlighting the importance of this receptor subtype during both health and disease states.